What Makes Tourist Experiences Interesting - Larsen, Svein; Wolff, Katharina; Doran, Rouven; Øgaard, Torvald (Frontiers in Psychology, 2019)
Traditional tourist role theory implies that tourists are either novelty seekers or familiarity seekers, while the interaction-hypothesis-of-inherent-interest predicts that interestingness is maximal when novel and familiar elements simultaneously are present in the experience. This paper tests these conflicting theoretical perspectives. In Study 1 (N = 1029) tourists were asked about their preferences for meeting tourists from their home country (familiar) or from a foreign country (unfamiliar), either at home (familiar) or abroad (unfamiliar). These preferences were observed in familiarity seekers and novelty seekers. Study 2 (N = 760) asked tourists to indicate the interestingness of well-known (familiar) and unknown (unfamiliar) sights at home (familiar) and abroad (unfamiliar) in familiarity seekers and novelty seekers alike. In Study 3 (N = 1526) tourists rated interestingness of familiar and unfamiliar attractions in familiar and unfamiliar surroundings for either themselves or for other tourists. Results show that perceived interestingness of tourist experiences depends on a combination of familiarity and novelty, for both familiarity seekers and novelty seekers. These results therefore are supportive of the interaction-hypothesis-of-inherent-interest; seemingly cognitive factors are better predictors of interestingness of tourist experiences than personality is.